(untitled) (International Journal of Engineering and Computer Science, 2015)
In the OFDM communication system the main disadvantage factor is Peak Average to Power Ratio (PAPR) which limits the performance of the overall system. To limit this factor in the OFDM system there are so many techniques are there, depends on the nature of the system like clipping, Partial transmission, Selective mapping, Companding transform etc, in these technique companding technique is the a simple methodology to compress or compand the input signal based on the inflection points to reduce the PAPR in the system, while decompander is the technique in the receiver to expand the companded signal from the transmitter section in the OFDM. The piecewise linear companding is based on the linear equations to compress the OFDM sequence where the companding distortion should considered, in this paper we present a efficient companding based on the piecewise linear equations. The whole system considered under ETU channel model. The simulation results show that a reduced PAPR and optimal BER rate of the OFDM system.